Perubahan Hasil Belajar Pendidikan Agama dan Budi Pekerti melalui Penerapan Teknik Pomodoro pada Siswa Kelas IX - Nurul Qomariyah; Muliatul Maghfiroh (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – The purpose of this study was to examine changes in students’ learning outcomes in Islamic Education and Character Education after implementing the Pomodoro technique among ninth-grade students.Methods – This study employed a quantitative, pre-experimental approach using a one-group pretest–posttest design with 30 ninth-grade students (n = 30).Findings – Analyses of 30 students’ results indicated a significant improvement in learning outcomes following the implementation of the Pomodoro technique. The mean pre-test score was 47.67, whereas the mean post-test score increased to 80.67. A paired-samples t-test yielded t = -9.912 with p = 0.001 (< 0.05). The Cohen’s dz value was 1.81, indicating a very large effect size. Based on these findings, it can be concluded that the implementation of the Pomodoro technique led to a significant improvement in ninth-grade students’ learning outcomes in Islamic Education and Character Education at SMPN 2 Larangan. Research Implications – Based on the study results, the implementation of the Pomodoro technique was associated with a significant improvement in PABP learning outcomes. These findings suggest that the Pomodoro technique can serve as an alternative instructional strategy for Islamic Education and Character Education teachers to help students manage study time, maintain focus, and reduce boredom.